PKM Penenun di Desa Barung-Barung Kecamatan Lima Puluh Kabupaten Batubara - Armaini Rambe; Fauzia Agustini; Dita Amanah; Dedy Ansari Harahap (Universitas Medan Area, 2019)
This article aims to increase partners' knowledge and skills in utilizing songket woven fabric. Reject coal, make online management and marketing systems effective. The method of activities is carried out in the form of assistance through counseling and training stages with lecture methods, question and answer, demonstrations which include preparation, implementation and evaluation. To determine the level of success of activities carried out monitoring and evaluation can be seen during preparation, process and end of the activity. The first meeting included preparation and planning, during the implementation phase counseling included knowledge of using reject woven fabrics. Training on making tissue boxes, bags, wallets and tablecloths, business management and assisting partners in training to market products online. The results of the activities of Partners 1 and 2 already have the knowledge and skills to make various bags, wallets and tablecloths. compile simple business management and make cash books and partners already have a website and utilize online media as a means of marketing products. Products are arranged in the Coal Workshop Cluster and Creative House. Various souvenir products have been exhibited at various national exhibition events. The impact of the activities of weavers was able to increase the economy and reduce unemployment in the Coal District. This can be seen from several residents who have joined the business.